Artificial Intelligence in Saudi Classrooms: Bridging the Gap Between Technology and Learning - العماري, عبدالله (مجلة جامعة الملك عبدالعزيز: العلوم التربوية والنفسية, 2025)
Abstract The rapid digital transformation in Saudi Arabia's higher education landscape has prompted a critical examination of integrating artificial intelligence (AI) tools and student perceptions. This study investigates university students' attitudes, technological readiness, and engagement with AI technologies within the unique sociocultural and educational context of Saudi Arabia. By employing a mixed-methods approach, the research provides nuanced insights into how emerging technologies are perceived, utilized, and potentially transformed in Saudi academic environments.